Magnetic resonance imaging and transient elastography in the management of Nonalcoholic Fatty Liver Disease (NAFLD). Issue 4 (3rd April 2017) - Han, Ma Ai Thanda; Saouaf, Rola; Ayoub, Walid; Todo, Tsuyoshi; Mena, Edward; Noureddin, Mazen
ABSTRACT: Introduction : Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and cirrhosis worldwide and the second most common cause of liver transplantation in major medical centers. Because liver steatosis and fibrosis severity are related to disease morbidity and mortality, the extent of disease, and disease progression, they need to be assessed and monitored. In addition, innovation with new drug developments requires disease staging and monitoring in both phase 2 and 3 clinical trials. Currently, disease assessment in both clinical practice and research is mostly performed by liver biopsy, an invasive, procedure with risks. Noninvasive, highly accurate tests are needed that could be used in clinical trials as surrogate endpoints and in clinical practice for monitoring patients. Area Covered : We discuss noninvasive tests, transient elastography (TE) with controlled attenuation parameter (CAP), magnetic resonance imaging (MRI), and MR elastography (MRE), summarize the available evidence of their usefulness for assessing steatosis and fibrosis. Therefore they could be used as clinical trials outcomes and in disease monitoring in clinical practice. Expert Commentary : TE with CAP, MRI and MRE are highly accurate noninvasive diagnostic tools for quantifying hepatic steatosis and fibrosis. Therefore they could be used as clinical trials outcomes and in disease monitoring in clinical practice.